The first occurrence of the enigmatic archosaur Crosbysaurus (Heckert 2004) from the Chinle Formation of Southern Utah - Gay,Robert J; St. Aude,Isabella (PeerJ PrePrints, 2014)
Originally identified as an ornithisichian dinosaur, Crosbysaurus has been found in New Mexico, Arizona, and the type locality in Texas. The genus has been reassessed by other workers in light of revelations about the postcrania of another putative Triassic ornithischian, Revueltosaurus. The understanding of Triassic dental faunas has become more complicated by the extreme convergence between pseudosuchian archosaurus and ornithichian dinosaur dental morphologies. We report here on a new specimen of Crosbysaurus from the Petrified Forest Member of the Chinle Formation at Comb Ridge in southeastern Utah. This new specimen is assigned to Crosbysaurus on the basis of the unique compound posterior denticles, mediolateral width, and curvature. While this specimen, MNA V10666, does not help resolve the affinities of Crosbysaurus it does represent an approximately 250 kilometer extension of the geographic range of this taxon. This is the first record of this taxon in Utah and as such it represents the northernmost known record of Crosbysaurus. This indicates that Crosbysaurus was not limited to the southern area of Chinle/Dockum deposition but instead was widespread across the paleoriver systems of the Late Triassic in western Pangea. The specimen we report on here was found in close association with a typical Late Triassic Chinle fauna, including phytosaurs, metoposaurs, and dinosauromorphs.
Keywords: Crosbysaurus; Chinle Formation; Chinle; Utah; Comb Ridge; new occurance; new record; Triassic; Late Triassic; archosaur